Sosa v Alvarez-Machain and The Alien Tort Claims Act - King, Hugh (Victoria University of Wellington Law Review, 2006)
Since the seminal case of Filartiga v Pena-Irala in 1980, the controversial Alien Tort Claims Act has regularly been invoked in United States federal courts to sue foreign perpetrators of international human rights violations. In Sosa v Alvarez-Machain, decided in 2004, the United States Supreme Court for the first time ruled on the Act’s proper application. This article, after first identifying three different approaches taken towards the Act by federal courts over the last 25 years, examines the Supreme Court decision. While welcoming the Court’s affirmation of the Act as a mechanism for addressing certain international law violations, it critiques the Court’s conservative and problematic test to determine the extent of the international law violations falling within the Act’s ambit, and highlights many ambiguities in the decision with which lower courts will have to grapple.